Hiatal hernia types and their radiological diagnostics in patients with gastroesophageal reflux disease - A. O. Nykonenko; Ye. I. Haidarzhi; T. V. Letkeman (Zaporožskij Medicinskij Žurnal)
Gastroesophageal reflux disease (GERD) is one of the most common gastrointestinal pathology. In more than 80–90 % of patients, GERD is caused by the presence of hiatal hernia, leading to the failure of the lower esophageal sphincter. Therefore, experts increasingly agree that GERD can be effectively treated surgically in this case with a detailed diagnosis and assessment of hiatal hernia types. One of the most common methods for diagnosing hiatal hernia is radiological. But the results of the data interpretation obtained during preparation for surgical treatment are contradictory. This situation requires work continuation in this direction.